MODELLING OF THE EFFECT OF TEMPERATURE AND DURATION OF OVER-EXPRESSION INDUCTION TO THE SOLUBILITY OF ZIKA VIRUS MULTI-EPITOP E PROTEIN IN Escherichia coli BL21(DE3) - Muchammad Gumilang, Danang
Zika virus is an Arbovirus from the Flaviviridae family that in the last decade has caused epidemics in several countries of Latin American and the Polynesian Islands. To date, the most common method used to detect Zika Virus’s infections is the serological test. However, the existing serological tests have not been able to provide specific results because of the cross reactivity which leads to false positives. In the previous study conducted by Kevin, 2018., the construction of Zika Virus’s E multi-epitope protein + L18 has been developed as a more specific antigen candidate. In the development roadmap of diagnostic kit, the antigen is required in soluble form and high quantity for better efficiency of production and ease the purification proces. However, most of the target protein expressed in E. coli BL21 system (DE3) is in the insoluble fraction. Two factors that are thought to be very influential on solubility of recombinant proteins are temperature and duration of induction. This research’s aim is to determine the effect of temperature and duration of induction, as well as the most optimum value of both factors in producing dissolved target protein by modeling the effect of temperature and duration of the induced overexpression of the protein solubility multi-epitope E Virus Zika + L18 using Response Surface Methodology (RSM) based on Face-Centered Central Composite Design (FC-CCD). The study began by reconfirming the presence of the E multi-epitop + L18 gene in stock culture using PCR method. Visualization results with agarose gel electrophoresis showed that there was a band that was suspected to be the E multi-epitope protein gene + L18 in the size range of 750-1000 bp. The visualization match with the In-Silico data prediction which stated that the size was 882 bp. Furthermore, to confirm its ability to express the target protein, culture was grown at 37oC for 3 hours. Visualization results using the SDS-PAGE method show that there is a band in the range slightly above the 25 kDa ladder size that is suspected to be the target protein, in contrast to the prediction using ExPASy which predicts a protein size of 24 kDa. The discrepancy between SDS-PAGE result and In-Silico prediction is thought to be caused by the gel shifting phenomenon. Modeling with RSM is done using three levels of each factor. The temperature levels used are 16oC, 27.5oC, and 39oC, while the duration of induction levels used are 6 hours, 16 hours and 26 hours. Before being visualized by the SDS-PAGE method, the concentration of dissolved protein from the expression results was normalized to 0,34 mg/mL. The results of visualization with SDS-PAGE were quantified using ImageJ software and analyzed with Design Expert 11 software. ANOVA analysis showed that the quadratic model constructed with Design Expert 11 was significant with a p-value <0,0001. The RSM analysis also shows that temperature is significant and positivelyinfluences the dissolved protein fraction, in contrast to the duration of induction which has a significant negative effect. The results showed that the optimum temperature and duration of induction conditions for obtaining soluble protein fraction was at 39oC and duration of induction for 6 hours, with the predicted results of the percentage of dissolved fraction being 27.577